Comparison of chemical and biological properties of organometallic complexes containing 4- and 5-nitrothienyl groups. (1st January 2021) - Toro, Patricia M.; Oyarzo, Juan; Arancibia, Rodrigo; Wilkinson, Shane; Artigas, Vania; Fuentealba, Mauricio; Moncada-Basualto, Mauricio; Olea-Azar, Claudio; Vega, Andrés; Hugo Klahn, A.
Graphical abstract: Organometallic imines containing 4- and 5-nitrothiophene were prepared and characterized by conventional spectroscopy and X-ray crystallography. The EC50 values obtained against T. b. brucei and T. cruzi indicate that 5-nitrothiophene derivatives were more active than 4-nitrothiophene analogues. These results agree with E 1/2NO2 values and with NO2 group Mulliken charges calculated. Highlights: Cyrhetrenyl and ferrocenyl imines containing isomeric nitrothienyl moieties were synthetized. The molecular structure of organometallic compounds (1a, 2a, and 3a ) was determined by single-crystal XRD. The anti-parasitic activities of all complexes were investigated. Theoretical studies about the nitro group position correlate with the anti-parasitic activity. Abstract: This study compares the nitro group position of thienyl imines bound to organometallic fragments, and the respective electrochemical and anti-parasitic properties. Ferrocenyl and cyrhetrenyl imines derived from 4-nitrothiophene (1a -3a ) and 5-nitrothiophene (1b -3b ) were synthesized and characterized by spectroscopic techniques. In addition, molecular structure of 1a, 2a and 3a were determined by X-ray crystallography. The reduction potential of the nitro group ( E 1/2 ), determined by cyclic voltammetry, shows that imines with a 5-nitrothiophene moiety exhibit lower E 1/2 values ( E 1/2  = −0.56 to −0.78 V) than 4-nitro derivatives ( E 1/2  = −0.92 to −1.04 V), indicating that 5-nitro compounds better generate radical species. The 5-nitrothiophene derivatives (1b -3b ) were more active against T. b. brucei (trypomastigotes) and T. cruzi (epimastigotes) than 4-nitrothiophene analogues (1a -3a ). Enhanced trypanocidal properties in 5-nitrothiophenes may be due to NO2 group reduction being readily converted to their downstream, trypanocidal products. Based on the anti-parasitic activity and Selectivity Index determined for all derivatives, 1b emerged as an appropriated agent for treatment of trypanosomal infections. Additionally, evaluations of T. b. brucei susceptibility showed that compound 3b is a substrate for TbNTR1. Density Functional Theory (DFT) calculations were used as an approximation to rationalize the influence of nitro group positions on the heterocyclic ring regarding electrochemical behaviour and anti-parasitic activity.